2014
DOI: 10.1186/1475-2840-13-9
|View full text |Cite
|
Sign up to set email alerts
|

High serum C1q-binding adiponectin levels in male patients with acute coronary syndrome

Abstract: BackgroundThe complement system is part of the immune system in acute coronary syndrome (ACS). Adiponectin has anti-atherogenic and anti-inflammatory properties. Adiponectin and C1q form a protein complex in blood, and serum C1q binding adiponectin (C1q-APN) can be measured. We investigated the comparative evaluation of serum C1q-APN levels in males with ACS, stable angina pectoris (SAP) versus controls.MethodsThe study subjects were 138 Japanese patients who underwent diagnostic coronary angiography. Blood to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…The amount of C1q–APN complex was significantly higher in the blood of patients with CAD than in the controls with no CAD. Our result is concordant with the other study that serum C1q-APN levels were significantly higher in the acute coronary syndrome than in the normal coronary group [ 26 ]. Recently, the protein family C1q/TNF-related protein (CTRP) has been discovered as adiponectin paralog.…”
Section: Discussionsupporting
confidence: 94%
“…The amount of C1q–APN complex was significantly higher in the blood of patients with CAD than in the controls with no CAD. Our result is concordant with the other study that serum C1q-APN levels were significantly higher in the acute coronary syndrome than in the normal coronary group [ 26 ]. Recently, the protein family C1q/TNF-related protein (CTRP) has been discovered as adiponectin paralog.…”
Section: Discussionsupporting
confidence: 94%
“…The increased C1q activity inhibited local inflammatory response in peripheral blood by combining with adiponectin. Therefore, it is an active defense against acute cardiovascular events and helps maintain autoimmune tolerance ( 55 ). Regrettably, ROC curve suggested that the accuracy in CAD by serum complement C1q activity was low.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PGZ addition enhanced the mRNA expression of PPARγ , PGC-1α and FABP3 , demonstrating an upregulated transport and accretion of fatty acids in the muscle of PGZ-fed animals. As a PPARγ agonist, PGZ has been shown to enhance the secretion of adipokines and increase adipocyte differentiation of progenitor cells ( Czarnowska et al., 2016 ; Kishida et al., 2014 ). Moreover, the IMF also increased in the longissimus thoracis muscle by activating PGC-1α and FABP3 ( Chen et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%